RORα phosphorylation by casein kinase 1α as glucose signal to regulate estrogen sulfation in human liver cells - Hu, Hao (Biochem J, 2020)
Estrogen sulfotransferase (SULT1E1) metabolically inactivates estrogen and SULT1E1 expression is tightly regulated by multiple nuclear receptors. Human fetal, but not adult, livers express appreciable amounts of SULT1E1 protein, which is mimicked in human hepatoma-derived HepG2 cells cultured in high glucose (450 mg/dl) medium. Here, we have investigated this glucose signal that leads to phosphorylation of nuclear receptor RORα (NR1F1) at Ser100 and the transcription mechanism by which phosphorylated RORα transduces this signal to nuclear receptor HNF4α, activating the SULT1E1 promoter. The promoter is repressed by non-phosphorylated RORα which binds a distal enhancer (−943/−922 bp) and interacts with and represses HNF4α-mediated transcription. In response to high glucose, RORα becomes phosphorylated at Ser100 and reverses its repression of HNF4α promoter activation. Moreover, the casein kinase CK1α, which is identified in an enhancer-bound nuclear protein complex, phosphorylates Ser100 in in vitro kinase assays. During these dynamic processes, both RORα and HNF4α remain on the enhancer. Thus, RORα utilizes phosphorylation to integrate HNF4α and transduces the glucose signal to regulate the SULT1E1 gene in HepG2 cells and this phosphorylation-mediated mechanism may also regulate SULT1E1 expressions in the human liver.